2022
DOI: 10.1016/j.cjco.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Delivery Outcomes Among Women With Peripartum Cardiomyopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…During the study time period, the prevalence of arrhythmia increased greatly for both Black and White pregnant individuals from 76.59/100,000 to 188.70/100,000 for Black (a 146% increase) and 55.49/100,000 to 179.19/100,000 for White (a 225% increase). Our results are in line with other NIS studies which have shown that Black pregnant individuals face a disproportionate burden of preeclampsia, peripartum cardiomyopathy, and severe maternal morbidity ( 24 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…During the study time period, the prevalence of arrhythmia increased greatly for both Black and White pregnant individuals from 76.59/100,000 to 188.70/100,000 for Black (a 146% increase) and 55.49/100,000 to 179.19/100,000 for White (a 225% increase). Our results are in line with other NIS studies which have shown that Black pregnant individuals face a disproportionate burden of preeclampsia, peripartum cardiomyopathy, and severe maternal morbidity ( 24 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…68 In an analysis of the National Inpatient Sample, after adjustment for clinical and socioeconomic factors, Black and American Indian/Alaska Native women had greater odds of developing peripartum cardiomyopathy compared with White women. 69 More data are needed in this area to better inform risk stratification tools and preventive strategies for these women. For select patients with advanced heart failure, heart transplantation remains the gold standard therapy to improve quality of life and survival.…”
Section: Maternal Heart Failure Outcomes In American Indian/alaska Na...mentioning
confidence: 99%
“…An article has shown that pregnant women with COVID-19 who are of non-White ethnicity, older, overweight, and have pre-existing maternal conditions like chronic hypertension and diabetes, as well as pregnancy-related complications, such as gestational diabetes and pre-eclampsia, are at a higher risk for severe COVID-19, admission to an intensive care unit, invasive ventilation, and maternal death [36]. Additionally, women who had pre-existing diabetes mellitus were reported to have almost twice the possibility of contracting COVID-19 [37]. The increased risks for pregnant women with diabetes emphasize the importance of taking necessary precautions to prevent contraction and ensure a safe pregnancy.…”
Section: Underlying Conditionsmentioning
confidence: 99%